Dental pathology and macrowear: a biocultural analysis of southern African holocene hunter-gatherers and hunter-herders - Olszewski, Judyta (Department of Human Biology, 2025)
Dental macrowear quantity, direction, and oral pathology were assessed against demographic factors in southern African Holocene hunter-gatherers and -herders (sAHGH). This is the first study to investigate inter-related implications of diet, health, and behaviour across time and space using only teeth on a large sAHGH sample. This aim was accomplished through a systematic assessment of macroscopic dental examinations, particularly including direction, a method not yet addressed for sAHGH teeth. Data were obtained using a multimethod approach on 369 individuals and 6271 teeth and statistically analysed using R (version 4.1.3) and IBM© SPSS. The results showed a need for an adaptation of the Brabant index; therefore, I created a novel adaption to the method inclusive of a visual guide. Individuals were better preserved from coastal regions (n = 313) and young/middle-ages (n = 71), and sex and temporal divisions were similarly distributed, with fewer individuals dating to the earlier Holocene (n = 50). Wear quantity advanced rapidly, with increased odds in anterior teeth (OR=18, p≤0.01) and first molars (OR=4.6, p≤0.01). Horizontal and plane wear directions frequently occurred (n = 8321 teeth), and combined wear results reflected a plant-based diet and using teeth as tools. Tool use was further demonstrated by non-masticatory wear (n = 22) and microchipping (n = 55), elucidating behaviours such as occupational tasks and dental hygiene. Generally, the teeth demonstrated good health; however, the first molar was affected most frequently with antemortem tooth loss (OR=13.6, p≤0.01), infections (OR=4.4, p≤0.01), and caries (OR=28.7, p≤0.01). Overall, pathological lesions post-2000 BP reduced, suggesting health improvements. Notably, incidence rates for enamel hypoplasia on the first molars (n = 26) alluded to increased infant stress possibly related to herding. Interestingly, amelogenesis imperfecta was found, demonstrating a hereditary condition associated with comorbidities. Despite increasing oral pathology and wear into old age, good survival rates suggest biological resilience. The results of this study support resource-sharing practices regardless of developmental stage between sexes, as sAHGH retained homogeneous diets and labour-based contributions from childhood. This research contributes to holistic inferences on health and behaviour through the direct analyses of sAHGH, integrating biology with the environment, and elaborates on the discussion of the role of dental wear and behaviours contributing to pathology susceptibility. A macroscopic, multimethod approach proved effective in analysing the interplay of masticatory mechanisms and systematic assessments using non-destructive methods. These results demonstrated how hunter-gatherer groups thrived over millennia, and that sAHGH are a good adaptive representation of dental analyses for precontact populations